Designing negative derivative feedback controller based on maximum damping and H2 method. (1st July 2022) - Jamshidi, Rasa; Collette, Christophe
Abstract: In this paper, a straightforward procedure is presented for optimal design of negative derivative feedback (NDF) controller with maximum damping and H 2 optimization method. NDF is a controller, which works as a band-pass filter, cutting off the control action far from the natural frequencies associated with the controlled modes and reducing spillover effect. Since it is a bandpass filter, it can effectively control the lower or higher frequency disturbances. It is also implementable on vibration mitigation applications with high performance. For this end, a simple one degree of freedom system is considered and afterward, the controller parameters are extracted dependent on closed loop damping. The H 2 method is used to calculate the optimal value of closed loop damping. The effect of changing the controller parameters on the system response are evaluated and discussed in detail. Also, the control effort for various closed loop damping has been calculated and compared with performance index of controller. A detailed comparison between performance and control effort are also presented. The results show high impact of NDF controller on vibration mitigation and its applicability to employ on various systems.